How to prosper during the coming bad years : - Ruff, Howard J. (Times Books, 1978)
This book is a basic survival guide for the battered pocketbook of the average American today. Conventional thinking about savings plans, insurance policies and other " safe " investment plans, and even the future value of pensions and social security are obsolete as the buying power of the dollar continues to drop at a rate unprecedented in recent history.